2018
DOI: 10.1021/acs.jced.7b00971
|View full text |Cite
|
Sign up to set email alerts
|

Viscometric Studies of Molecular Interactions in Binary Liquid Mixtures of Isomeric Xylenes with Methanol

Abstract: Dynamic viscosities (η exp ) for the binary mixtures of methanol with isomeric (o-, m-, and p-derivatives) xylenes were measured at T = (303.15, 308.15, 313.15, 318.15, and 323.15) K and atmospheric pressure (p = 101 kPa). The viscosity deviation (Δη) that has been derived from the η exp was correlated using a Redlich− Kister-type equation. The η exp values were compared with the calculated viscosities (η cal ) obtained using generalized correlation models, such as Bingham, Arrhenius, Kendall−Monroe, Grunberg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…From the experimental values of viscosity (η) and density () of binary mixture: TBP + benzene, the theoretical values of viscosity were estimated by using the following five different mathematical relations of zero adjustable parameters [13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the experimental values of viscosity (η) and density () of binary mixture: TBP + benzene, the theoretical values of viscosity were estimated by using the following five different mathematical relations of zero adjustable parameters [13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…The observed deviations of the theoretical dynamic viscosity from the experimental values ( Fig. 1 and Table 3) may be due to the presence of intermolecular interactions between the component molecules of the mixture [13][14][15]. The suitability of these theories based on APD and RMSDr values is as follows…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, considering the ultrasonic velocities and their related parameters, this system was chosen to under a better knowledge of the nature of interactions between dimethyl malonate and isomeric xylenes. An extensive study on the excess qualities has been reported on the properties of o-xylene with propan-2-ol, butan-2-ol and pentan-2-ol [7], 2-butanol + m-xylene [8], poly(propylene glycol) + toluene/o-xylene/m-xylene/p-xylene [9], isomeric xylenes and diethyl malonate [10], methanol with o, m and pxylenes [11], cyclohexane with toluene, o-xylene and mesitylene [12], xylene and certain alkanols (C4-C8) [13], dimethyl formamide (DMF) with benzene, o-xylene, 1,4-dioxane and tetra hydrofuran [14], 1,4-dioxane with o-, m-, p-xylene, toluene, benzene and mesitylene [15], benzene, toluene, o-, m-, p-xylene and mesitylene with 1,4-dioxane [16], ethylbenzene + p-xylene [17], quinolone + m-xylene [18] and o-xylene with ethyl oleate [19].…”
Section: Introductionmentioning
confidence: 99%
“…27 Chen et al reported the refractive index of an aqueous solution of CdTe quantum dots. 28 As a continuation of our previous research on thermodynamic and optical behavior of some binary liquid mixtures, [29][30][31][32] this paper presents new experimental data of refractive index for two binary systems of methyl acetate (MAc) + methyethanolamine (MEA), and + dimethylethanolamine (DMEA) at T = 293.15, 303.15, and 313.15 K under atmospheric pressure, over the entire mole fraction range. Refractive index measurements are expected to insight both solvent-solvent and solute-solvent interactions.…”
mentioning
confidence: 99%